Smart fan / Muhammad Yusoff Syah Zakaria & Tengku Ahmad Nazirulmubin Tengku Md Sa'abri - Zakaria, Muhammad Yusoff Syah; Tengku Md Sa'abri, Tengku Ahmad Nazirulmubin (2015)
Our project which is the Smart Fan is a device that can read the surrounding temperature and change the speed of the fan based on the temperature detected. This device will give a lot of benefit to the all kind of people and even the industries. Our device is to be used worldwide. This Smart Fan can also give reading of the surrounding temperature and display the speed of the fan in real time. Besides, the Smart Fan helps people helps people to stay comfortable by reducing the heat around them and stabilize the surrounding temperature by changing the speed of the fan.